Adaptation of the children of migrant workers to the new social and cultural space: pedagogical help and support - Nataliia Sabat (Vasyl Stefanyk Precarpathian National University, 2017)
The article substantiates the value of the pedagogic help and support in the adaptation of migrants to the new circumstances of social and cultural space. The basic needs of the children from the specified category are characterized, and if we meet these needs will have the successful adaptation. The essence of information, instrumental emotional support was revealed. It was proven that the school serves the important medium to conduct such activities as the usual environment where a child with a family of migrants stays, talks, feels comfortable. The necessity of the cooperation between the teachers, educators, social educator and psychologist, administration is emphasized in helping the children of migrant workers in the process of adapting to the new social and cultural space. Key words: children of migrants, adaptation, educational help, pedagogic support, social and cultural space.